How Information Is Presented in Financial Reports and the Usefulness of the Forms Chosen – a Review of Selected Research - Kędzior, Marcin; Grabiński, Konrad (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The purpose of the research was to gather and present arguments available in the subject literature which support the thesis that how financial statements are presented impacts their usefulness. The basic research method was an analysis of Polish and international literature on the subject, with the article then summarising the results of empirical studies done by other authors. In the majority of cases the problem was analysed in the context of financial statements prepared under the Polish Accounting Act, IAS/IFRS and US GAAP. The first issue addressed is the aggregation and disaggregation of items reported in financial statements. The study also examines the presentation of financial statements prepared by IASB and FASB. The analysis of the literature and the studies presented together show that the form in which financial statements are presented has a profound impact on their usefulness.